(untitled) (Journal of the College of Basic Education, 2022)
Regional studies are one of the most important topics of interest to geography in general. The study of the functional region of a phenomenon is based on the dynamic interaction and functional interdependence between the studied site and the surrounding regions. Geography is characterized by its ability to analyze the movement of jobs carried out by cities, their influence trends, the areas to which the services of these jobs reach, and the extent of their interaction with their near or far regional surroundings. The city offers its residents and the residents of the surrounding regions, and its regional impact increases whenever the scientific specialization required to be studied at the college is rare and requires a high rate of admission. The most important measure by which nations measure their progress and are reassured about their future is the measure of the scientific arsenal, represented by young scientists under the age of 30, and the more they possess a repertoire of creators, the greater their chance of development and progress (1). Given the importance of the College of Engineering For students, it provides them with practical and technical skills to solve problems and gives the student knowledge in the field of mathematics, science, design, maintenance, production ... etc. It also provides engineering students with technological solutions to problems, issues and ideas that affect every aspect of life. For all this, the College of Engineering was chosen at the Iraqi University, which is located in the city of Baghdad, which is considered one of the cultural, social, cultural and locational pillars. Until the year 2020. We have relied on the data available at the Registration Department at the college in order to achieve the goal of the research. The statistical method was also used to tabulate this data, extract percentages for it, and clarify the results through the figures, and then project them overall on the map in order to draw the borders of the region and know the geographical extension of these The college is within the areas under its influence.